2020
DOI: 10.3747/co.27.5875
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Humour in Oncology: A Survey of Patients Undergoing Radiotherapy

Abstract: Background: Humour has long been considered an important coping tool for patients with cancer, but published quantitative data about its significance are limited. The purpose of our study was to survey patients with cancer undergoing radiotherapy regarding their opinions about the use of humour in their care. Methods: An anonymous 35-item questionnaire evaluating the patient experience, including the value of humour, was developed by an interdisciplinary team of health care providers (HCPS) working within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…(b) what is the role of humor in brain cancer caregiving? Given the paucity of research exploring caregiver strengths, it is hoped that the findings will reinforce recent calls in the wider oncology literature for those invested in cancer care to “wake-up” to the importance of humor and laughter (Samant et al, 2020, p. 353).…”
Section: Introductionmentioning
confidence: 79%
“…(b) what is the role of humor in brain cancer caregiving? Given the paucity of research exploring caregiver strengths, it is hoped that the findings will reinforce recent calls in the wider oncology literature for those invested in cancer care to “wake-up” to the importance of humor and laughter (Samant et al, 2020, p. 353).…”
Section: Introductionmentioning
confidence: 79%
“…The results of this study showed how fundamental the use of humor is in interpersonal interactions, even within a pain management setting. The deliberate application of humor to difficult situations has been demonstrated in other chronic illness populations; after radiotherapy, humor enabled people with cancer to cope better with their health ( 38 ). Similarly, quantitative assessment of humor use within pain, has suggested that PLwCP may employ humor to gain perspective on their pain and distance themselves from their situation by accepting the negative emotions that common when living with chronic pain ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prosocial nature of the humor demonstrated in this study was unusual in that it employed mutual sarcasm, with the sarcasm applied not to a person, but to the context under discussion-chronic pain itself. Wider literature suggests that the type of humor is important when addressing health conditions ( 47 , 48 ) for example, mocking and sarcasm are typically viewed negatively ( 38 ). However, in this study, the participants used sarcasm that was received positively and was directed toward pain rather than a person or their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, como afirma SAMANT et al (2020), o humor tem sido uma parte da civilização e requer habilidade, uma vez que os indivíduos hospitalizados já estão em uma situação complexa. Nessa perspectiva, a experiência da doença pode causar sentimentos e sensações de impotência e tristeza nos pacientes, interferindo diretamente nas emoções e no bem-estar de cada indivíduo.…”
Section: Conclusãounclassified
“…Tanto no estudo feito porKURUDIREK et al (2020), que selecionou 74 crianças, 36 no grupo controle e 38 no grupo com exposição ao palhaço no ambulatório, quanto no estudo deSAMANT et al (2020), no qual observaram pacientes com câncer submetidos a radioterapia por meio de um questionário com 35 itens acerca da experiência, foi constatado o favorecimento da diminuição da ansiedade, alívio do estresse e melhora da comunicação. Entretanto, o humor deve ser individualizado e personalizado de acordo com o paciente e as circunstâncias.…”
unclassified